Obstructive Sleep Apnea Risk Level Affect Executive Function Rather than Attention (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Obstructive sleep apnea (OSA) is a kind of sleep disorders which is associated with cognitive impairment, either independently or by its strong association with metabolic syndrome. OSA affected attention and executive functions. Since the diagnosis of OSA had limitation, the assessment of OSA risk level by using STOP-BANG Questionnaire instrument in common population is important. This was a cross-sectional study aimed to investigate the effect of OSA risk level determined based on STOP-BANG Questionnaire score to attention and executive functions in 82 subjects. The demographic and clinical characteristics data obtained were age, gender, level of education, hypertension, body mass index (BMI), neck circumference, OSA risk level, and attention and executive functions.Â Attention function was assessed by using Forward Digit Span and Trailmaking Test A (TMT-A) instruments, while executive function was assessed by using Backward Digit Span and Verbal Fluency Test instruments. The demographic and clinical characteristics data showed significant higher proportion of male gender, large neck circumference, and hypertension in high risk OSA group. The OSA risk level significantly impaired the executive function but did not impaired attention function.